Germanene Nanosheets: Achieving Superior Sodium‐Ion Storage via Pseudointercalation Reactions. Issue 10 (28th July 2021) - Liu, Nana; Xu, Kang; Lei, Yaojie; Xi, Yilian; Liu, Yani; Wang, Nana; Wang, Yun-Xiao; Xu, Xun; Hao, Weichang; Dou, Shi Xue; Du, Yi
Abstract : The potential of germanium‐based anodes for sodium‐ion batteries (NIBs) is seriously hindered by the high diffusion barrier of Na ions in the Ge lattice. Herein, a massive and defect‐rich 2D germanene nanosheet based anode is fabricated and exhibits enhanced Na‐storage performance for NIBs. Unlike the typical alloying/dealloying reactions of crystalline Ge, the germanene nanosheets are converted to go through a pseudointercalation mechanism during charge/discharge processes. Accordingly, the diffusion energy barriers of sodium atoms in the germanene nanosheets are significantly reduced, leading to high Na‐storage activity. Combined with its large surface area, high mechanical flexibility, fast electron mobility as well as its defect‐rich structure, the germanene anode delivers an initial capacity of 695 mAh g −1, enhanced cycling performance, and outstanding rate capacities, compared with those of GeH nanosheets and Ge particles. It is believed that the germanene anode not only extends the scope of germanene application, but also provides new insights for adjusting Na‐storage pathways toward superior battery performance. Abstract : A massive and defect‐rich 2D germanene nanosheet based anode is fabricated and exhibits enhanced cycling performance and outstanding rate capacities compared with GeH nanosheets and Ge particles. Unlike the typical alloying/dealloying reactions of crystalline Ge, the germanene nanosheets are converted to go through a pseudointercalation mechanism during charge/discharge processes, providing new insight for adjusting Na‐storage pathways.